2016
DOI: 10.5812/ircmj.25116
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-Based Cognitive Therapy on Iranian Female Adolescents Suffering From Social Anxiety

Abstract: BackgroundSocial anxiety is one of the most common psychological disorders that exists among children and adolescents, and it has profound effects on their psychological states and academic achievements.ObjectivesThe aim of this study was to determine the effectiveness of mindfulness-based cognitive therapy (MBCT) on diminishing social anxiety disorder symptoms and improving the self-esteem of female adolescents suffering from social anxiety.Patients and MethodsSemi-experimental research was conducted on 30 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…MBI has been found to affect 'intolerance of uncertainty' and 'anxiety sensitivity' in patients with PD, 'worry' feature in those with GAD, low self-esteem in social anxiety patients and emotional self-regulation in depressed patients. 23, [35][36][37][38] Some studies have also demonstrated that the improvement in the depression and anxiety symptoms paralleled with improvement in the mindfulness. [47][48][49]51,57,60 However, studies that tested MBSR or its modified version and traditional meditation didn't demonstrate significant effect in depressive symptoms, for examples, 'Vipassana mindfulness approach' in alcohol dependent patients, MBSR for depression in prenatal depression, stress coping program based on mindfulness meditation and 'Mindfulness-Based Therapy and Counseling' (MBTC) in nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBI has been found to affect 'intolerance of uncertainty' and 'anxiety sensitivity' in patients with PD, 'worry' feature in those with GAD, low self-esteem in social anxiety patients and emotional self-regulation in depressed patients. 23, [35][36][37][38] Some studies have also demonstrated that the improvement in the depression and anxiety symptoms paralleled with improvement in the mindfulness. [47][48][49]51,57,60 However, studies that tested MBSR or its modified version and traditional meditation didn't demonstrate significant effect in depressive symptoms, for examples, 'Vipassana mindfulness approach' in alcohol dependent patients, MBSR for depression in prenatal depression, stress coping program based on mindfulness meditation and 'Mindfulness-Based Therapy and Counseling' (MBTC) in nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that MBCT also significantly improved self-esteem at the end of treatment. 37 A single RCT demonstrated MBSR to be effective in reducing anxiety, worry and depressive symptoms in participants with GAD. 38 A trial without control from India tested the efficacy of mindfulness-integrated cognitive behavior therapy (MiCBT) on participants with obsessive-compulsive disorder (OCD) with mild to moderate obsessive symptoms and no or minimal compulsions.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…This margin reflects the change in MAAS-A scores found in the initial validation study of the MAAS in adolescents using an in-person program [ 41 ]. Unfortunately, the convenient sample size of 60 participants used for this study will not allow sufficient power to demonstrate noninferiority of secondary outcomes assessed by standardized questionnaires, based on recent mindfulness studies using these measures in adolescent populations [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of mindfulness-based cognitive therapy (MBCT) on diminishing social anxiety disorder symptoms and improving the self-esteem of female adolescents suffering from social anxiety was determined [5]. Spatio temporal analysis approach useful for neuroscience researchhas been proposed [6].…”
Section: International Journal Of Chemtechmentioning
confidence: 99%